Weather in the city : how design shapes the urban climate - Lenzholzer, Sanda, ....- (Rotterdam : Nai010 publishers, 2015)
There is plenty of urban architecture whose design fails to take the urban climate properly into account: a beautifully laid-out square where you are nearly blown off your feet, or a modern city apartment that is too hot to sleep in during the summer. Weather in the City explains and illustrates how smart urban design can enhance comfort in the city. The way we experience the urban climate depends on physical and psychological factors dictated by our surroundings. How can spatial planning and urban design influence our experience of the weather? With practical case studies richly illustrated with photographs and diagrams, Weather in the City is both a reference work and a source of inspiration for all those working to enhance the quality of city life--from commissioners and policymakers to students in urban design, landscape architecture and planning.
Keywords: Duurzame Stedenbouw; Landschapsarchitectuur; Stadsontwikkeling; Stedenbouw